1999
DOI: 10.1094/mpmi.1999.12.12.1114
|View full text |Cite
|
Sign up to set email alerts
|

A Cysteine Protease Gene Is Expressed Early in Resistant Potato Interactions with Phytophthora infestans

Abstract: A potato cysteine protease (cyp) cDNA expressed at an early stage of an incompatible interaction with Phytophthora infestans was isolated. Both the nucleotide and deduced amino acid sequences are highly homologous to those of a tomato cysteine protease, CYP1. Striking protein similarity to all known cathepsins in animals, particularly cathepsin K, was also observed. However, unlike cathepsins, a granulin binding domain is located near the carboxyl terminus of the putative CYP protein. In animals, granulins bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 26 publications
4
58
1
1
Order By: Relevance
“…However, the identified potato Cys protease has a molecular mass of ;51 kD, which differs from the observed molecular mass of ;45 kD (Figure 9), suggesting the protein is posttranslationally modified or is the product of another gene not identified due to incomplete sequencing of the potato genome. In a previous report (Avrova et al, 1999), the putative Cys protease identified here was found to be tightly regulated and to be induced by Phytophthora infestans in potato leaves. Considering a high level of sequence similarity to cathepsin K and the existence of a granulin binding domain in the C terminus, the putative Cys protease has been proposed to have caspase-like regulatory function through a specific target mechanism of its granulin binding domain (Avrova et al, 1999).…”
Section: Pmc Affinity Protein From S Tuberosumsupporting
confidence: 55%
See 2 more Smart Citations
“…However, the identified potato Cys protease has a molecular mass of ;51 kD, which differs from the observed molecular mass of ;45 kD (Figure 9), suggesting the protein is posttranslationally modified or is the product of another gene not identified due to incomplete sequencing of the potato genome. In a previous report (Avrova et al, 1999), the putative Cys protease identified here was found to be tightly regulated and to be induced by Phytophthora infestans in potato leaves. Considering a high level of sequence similarity to cathepsin K and the existence of a granulin binding domain in the C terminus, the putative Cys protease has been proposed to have caspase-like regulatory function through a specific target mechanism of its granulin binding domain (Avrova et al, 1999).…”
Section: Pmc Affinity Protein From S Tuberosumsupporting
confidence: 55%
“…Analysis of the eluted proteins by SDS-PAGE revealed one predominant protein band of ;45 kD, a PMC-2 band of ;10 kD, and a number of less intense bands ( Figure 9). LC-MS/MS analysis detected three peptides, ID-SYEDVPVNNEK, AVAHQPVSIAIEAGGR, and NVASSSGLCGLA-TEPSYPVK, which were used to identify the predominant protein as a 466-amino acid putative Cys protease from S. tuberosum (Avrova et al, 1999).…”
Section: Pmc-2 Pull-down Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the existing reports come from physiological studies or gene expression from these enzymes under conditions of stress or pathogen attack [28,44].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the physiological functions of these peptidase. In plants, for example, they have been associated with the mobilization of nutrients and defence against pathogens [3,28,47]. Many of these enzymes have important applications in medicine and biotechnology.…”
Section: Discussionmentioning
confidence: 99%